Determinasi Keputusan Alumni Melanjutkan Studi di Universitas Asal: Peran Niat sebagai Mediasi Motivasi, Citra, dan Persepsi Kualitas Institusi - Rehulina Desviora Sitepu; Metta Padmalia (Journal of Economics and Management Scienties, 2026)
This study aims to analyze the factors influencing alumni decisions to pursue postgraduate studies by emphasizing the mediating role of intention. This research is motivated by a gap in previous studies, which generally position institutional image as a primary factor in higher education selection, yet remain limited in examining decisions to continue studies within the same institution, particularly in the context of alumni who already have direct experience with the institution. In addition, the declining proportion of alumni continuing their studies at their alma mater further underlines the importance of this study. A quantitative approach was employed, with data collected through a survey of 105 undergraduate alumni from a private university in East Java. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that study motivation and perceived institutional quality have a significant effect on the intention to pursue further studies, while institutional image does not have a significant effect. Furthermore, intention significantly influences the decision to pursue postgraduate studies, whereas the direct effects of study motivation, institutional image, and perceived institutional quality on the decision are not significant. These findings indicate that intention plays an important mediating role in the decision-making process to pursue further studies. The study suggests that higher education institutions should focus more on enhancing student motivation and engagement rather than relying solely on institutional image.